2013
DOI: 10.4314/ajid.v8i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Hepatitis C and Human Immunodeficiency Virus Coinfection among Children in Enugu, Nigeria

Abstract: Background: Hepatitis C virus (HCV) and Human Immunodeficiency virus (HIV), are major public health challenges in the developing world especially sub-Saharan Africa. The aim of this study was to determine the prevalence and risk factors of Hepatitis C virus infection among children infected with HIV. Methods: This was a cross-sectional study conducted at the Paediatric HIV Clinic, UNTH, Enugu between July and December 2009. Antibodies to HCV were analyzed by newer generation rapid chromatographic immunoassay m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 11 publications
2
16
1
Order By: Relevance
“…The seroprevalence of HCV in this study (5.5%) conforms to the estimated prevalence of HCV in Africa (5.3%), which is the highest in the world [ 26 ]. It is also comparable with reports from Nigeria (6.8%) [ 27 ]. Comparison was not possible in Ethiopian context owing to lack of HCV seroprevalence data in HIV infected children.…”
Section: Discussionsupporting
confidence: 91%
“…The seroprevalence of HCV in this study (5.5%) conforms to the estimated prevalence of HCV in Africa (5.3%), which is the highest in the world [ 26 ]. It is also comparable with reports from Nigeria (6.8%) [ 27 ]. Comparison was not possible in Ethiopian context owing to lack of HCV seroprevalence data in HIV infected children.…”
Section: Discussionsupporting
confidence: 91%
“…Similar studies from other countries recorded 4.6% in Brazil [1], 10.3% in Kenya [7] and 1.42% in Pakistan among pregnant women [13]. The high prevalence recorded in the study especially with no obvious efficient risk factor as reported by other researchers might be connected with the fact that the transmission efficiency is determined by the amount of virus in a body fluid and the type and extent of the contact [14]. Unfortunately unlike HBV, HCV does not have vaccine yet.…”
Section: Discussionsupporting
confidence: 85%
“…of HCV +ve experienced by this gender. Eze et al (2014) in Enugu also observed this but adduced it to the preferential care of the male child which may have exposed them to more risks of acquiring HCV as they are given both orthodox and non-orthodox treatment when sick. The significant risk factors for HCV positivity found among the studied cohort were blood transfusion.…”
Section: Discussionmentioning
confidence: 92%